Status of the WEST travelling wave array antenna design and results from the high power mock-up. (11th January 2022) - Ragona, R.; Durodié, F.; Messiaen, A.; Ongena, J.; Van Schoor, M.; Agzaf, S.; Batal, T.; Bernard, J.-M.; Courtois, X.; Delaplanche, J.-M.; Dumont, R.; Durand, F.; et al.
Abstract: This paper presents the current status of the WEST TWA antenna, its mock-up and a possible extrapolation to DEMO. The updated WEST TWA design has a reduced antenna length and features feeding and mechanical support from a single vessel port. A mock-up of the WEST TWA antenna was designed in 2019, manufactured during 2020 and installed in the TITAN test facility at the beginning of 2021. The results of the mock-up at low and high power, its diagnostic system and the prospects are explained. Extensions towards a TWA antenna for WEST and a possible TWA system for the future DEMO tokamak reactor are briefly discussed.